2016
DOI: 10.3389/fphar.2016.00087
|View full text |Cite
|
Sign up to set email alerts
|

Sex-Related Differences of Lipid Metabolism Induced by Triptolide: The Possible Role of the LXRα/SREBP-1 Signaling Pathway

Abstract: Triptolide, a diterpenoid isolated from the plant Tripterygium wilfordii Hook. f., exerts a unique bioactive spectrum of anti-inflammatory and anticancer activities. However, triptolide’s clinical applications are limited due to its severe toxicities. Fatty liver toxicity occurs in response to triptolide, and this toxic response significantly differs between males and females. This report investigated the pathogenesis underlying the sex-related differences in the dyslipidosis induced by triptolide in rats. Wis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
24
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(25 citation statements)
references
References 46 publications
1
24
0
Order By: Relevance
“…According to earlier reports, SREBP-1c plays a critical role in NASH progression and involves in tissue apoptosis [3,77], cell cycle control [78,79], transcription regulation [80], lipid metabolism [81,82], and many other life activities. All these are related to the development of NASH.…”
Section: Discussionmentioning
confidence: 99%
“…According to earlier reports, SREBP-1c plays a critical role in NASH progression and involves in tissue apoptosis [3,77], cell cycle control [78,79], transcription regulation [80], lipid metabolism [81,82], and many other life activities. All these are related to the development of NASH.…”
Section: Discussionmentioning
confidence: 99%
“…As a key regulator of detoxification and BA metabolism, Nrf2 induces a series of hepatic efflux transporters that aid in the elimination of potentially harmful endo- and xenobiotics ( Klaassen and Reisman, 2010 ; Zhang et al, 2017 ). Since TP-induced hepatotxicity is correlated with its hepatic exposure and BA accumulation which may lead to cholestatic symptoms ( Kong et al, 2015 ; Jiang et al, 2016 ; Yang et al, 2017 ), and licorice and its main constitutes have been proved to induce the expressions of an array of Nrf2 downstream transporters and inhibit chelostasis ( Wang X. et al, 2013 ; Gong et al, 2015 ), we measured changes in the expression of hepatic transporters after TP and ISL treatment. TP treatment reduced the expressions of MRP2 in vitro and in vivo , while ISL combined treatment reversed this effect.…”
Section: Discussionmentioning
confidence: 99%
“…Besides, since TP-induced hepatotoxicity is quantitatively correlated with the hepatic exposure to the parent drug, changes in pharmacokinetic profiles of TP may also influence its hepatotoxicity ( Kong et al, 2015 ), and CYP3A-mediated metabolism of TP is a detoxification pathway ( Xue et al, 2011 ). More recently, TP administration was found to increase the total bile acid (TBA) accumulation in rat livers ( Jiang et al, 2016 ; Yang et al, 2017 ), and activation of the BA receptor (FXR) ameliorates the TP-induced liver injuries ( Jin et al, 2015 ). Combined with the cholestatic symptoms of TP administration observed in clinics ( Xue et al, 2009 ), we speculate that besides the hepatic accumulation of TP, mechanisms involved in the change of endogenous BA profiles may as well contribute to TP-induced hepatotoxicity.…”
Section: Introductionmentioning
confidence: 99%
“…In TP-induced hepatotoxicity, sex-related differences in the toxicity of TP have received attention in recent years [42]. Female mice exhibit more severe toxicity than male mice [3]. Since sex is a fundamental biological variable that cannot be overlooked, only female mice were used in our toxicological research of TP.…”
Section: Discussionmentioning
confidence: 99%
“…Severe adverse reactions, however, especially hepatotoxicity, have greatly restricted its approval in the market. Although several published reports have demonstrated that TP causes liver injury by lipid peroxidation, stress responses, and hepatocyte necrosis [3,4], the underlying cellular mechanisms of TP-induced liver injury require more detailed investigations. Recently, it has been found that hepatocytes may not be the only target in drug-induced liver injury (DILI) [5].…”
Section: Introductionmentioning
confidence: 99%